A pair-wise analysis of the law of one price: Evidence from the crude oil market (2015)
This paper applies a pairwise approach to investigate the validity of the law of one price in the crude oil markets. Price differentials appear smaller between crude oil pairs with similar physical/chemical characteristics and also for pairs within OPEC. © 2015.